Interface modification layer for solid alkali metal negative electrode and preparation method and application thereof

By using a composite interface modification layer of lithiated fluoropolymer and highly dielectric nanoceramic material in all-solid alkali metal batteries, the problem of poor contact between the negative electrode/solid electrolyte is solved, and the electrochemical and mechanical properties of the battery is significantly improved, achieving efficient fast charging and long-term stable operation.

CN119833564APending Publication Date: 2025-04-15SVOLT ENERGY TECH (WUXI) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510133571.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-06
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

There is a poor contact problem in the negative electrode/solid electrolyte interface in all-solid alkali metal batteries, resulting in large interface resistance and uneven ion flux distribution, which promotes the formation and growth of metal dendrites, which in turn affects the safety and cycle life of the battery.

Method used

The composite interface modification layer of lithiated fluoropolymer and highly dielectric nanoceramic material is adopted to promote the rapid conduction of alkali metal ions through the fluoroelastic components of lithiated fluoropolymer and the characteristics of anchor anions; the high dielectric nanoceramic material promotes the uniform deposition of alkali metal ions through dynamic uniform electric field action, and avoids the growth and cracks of metal dendrites.

Benefits of technology

It significantly reduces the side reaction between the alkali metal negative electrode and the solid electrolyte, improves the lithium-ion conductivity and kinetic performance of the interface, and achieves good charging and discharge efficiency of all-solid alkali metal batteries under high current density, supporting fast charging and long-term stable operation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833564A_ABST
    Figure CN119833564A_ABST
Patent Text Reader

Abstract

The invention provides an interface modification layer for a solid alkali metal negative electrode and a preparation method and application thereof. The materials of the interface modification layer comprise a lithiated fluorine-containing polymer and a nano dielectric ceramic material. According to the interface modification layer provided by the invention, side reaction between the alkali metal negative electrode and the solid electrolyte can be effectively reduced, growth of metal dendrites and appearance of cracks can be slowed down, and the all-solid-state alkali metal battery can realize relatively good charge-discharge efficiency under high current density; therefore, quick charging and long-term stable operation of the all-solid-state alkali metal battery are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries, and in particular relates to an interface modification layer for a solid alkali metal negative electrode, and a preparation method and application thereof. Background Art

[0002] At present, the main disadvantages of alkali metal anode materials (such as lithium, sodium or potassium) in liquid electrolytes include uncontrollable dendrite growth and severe side reactions at the anode / liquid electrolyte interface. These problems lead to poor safety and short cycle life of alkali metal batteries, and further limit their commercial application. In recent years, solid electrolytes have been used as physical barriers to partially inhibit the interfacial side reactions of alkali metal batteries due to their good mechanical properties and electrochemical stability, thereby improving the electrochemical performance of alkali metal batteries.

[0003] However, unlike the solid-liquid interface in traditional liquid batteries, the negative electrode / solid electrolyte interface in solid-state batteries is a solid-solid interface, which has a significant poor contact problem. This solid-solid contact lacks wettability, resulting in a small contact area and poor contact tightness between the two, thereby forming a high interface resistance, which limits the transmission efficiency of alkali metal ions at the interface. In addition, defects such as voids, uneven purity, and uneven grain distribution on the surface of the solid electrolyte will affect the space charge layer, resulting in uneven distribution of ion flux, which in turn promotes the formation and growth of alkali metal dendrites, and may eventually lead to battery short circuit. Therefore, the interface problem of the negative electrode / solid electrolyte is one of the main challenges in achieving high-performance all-solid-state alkali metal batteries.

[0004] In order to solve the above problems, researchers have proposed a variety of strategies, including optimizing the mechanical properties of electrolyte materials or improving interface wettability. These methods aim to reduce interface impedance and improve interface stability, thereby improving the overall performance and safety of all-solid-state alkali metal batteries. For example, the prior art discloses the use of organic polymers with good flexibility to modify solid electrolytes to reduce interface impedance (reference: Adv. Energy Mater. 2021, 11, 2003469). Among them, the organic polymer layer can not only improve the physical contact performance of the interface, but also prevent electrons from entering the solid electrolyte. However, the organic polymer layer has a low ionic conductivity at room temperature, which is not conducive to the deposition / stripping process of alkali metal ions at high current density. In addition, the prior art also discloses the use of inorganic protective coatings (such as SnS2 or AlF3, etc.) to effectively reduce the interfacial contact between alkali metals and solid electrolytes. In fact, most inorganic interface layers still require the use of liquid electrolytes to wet the interface or use molten metals, which makes their application relatively complicated and not suitable for large-scale production.

[0005] Therefore, how to obtain an interface modification layer with high ionic conductivity and electronic conductivity to alleviate the interfacial side reactions between alkali metal anode materials and solid electrolytes and achieve a kinetically stable interface is crucial to solving the anode / electrolyte interface problem in all-solid-state batteries. Summary of the invention

[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide an interface modification layer for a solid alkali metal negative electrode and a preparation method and application thereof. The interface modification layer provided by the present invention can effectively reduce the side reaction between the alkali metal negative electrode and the solid electrolyte, and slow down the growth of metal dendrites and the appearance of cracks, and enable the all-solid-state alkali metal battery to achieve better charge and discharge efficiency at high current density, thereby achieving fast charging and long-term stable operation of the all-solid-state alkali metal battery.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides an interface modification layer for a solid alkali metal negative electrode, wherein the material of the interface modification layer comprises a lithiated fluorinated polymer and a nano dielectric ceramic material.

[0009] Aiming at the technical problem that the interface resistance between the alkali metal negative electrode and the solid electrolyte in the prior art is large due to poor interface contact, the ion flux distribution is uneven, which promotes the formation and growth of metal dendrites, resulting in poor rate performance and continuous capacity loss during the cycle of the all-solid-state alkali metal battery, and finally causes short circuit, the present invention aims to improve the electrochemical and mechanical properties of the all-solid-state alkali metal battery by combining the single-ion conductive lithium fluorine-containing polymer with a high dielectric nano-ceramic material. Among them, the lithium fluorine-containing polymer stabilizes the negative electrode through the fluorine-rich elastic component it contains, and promotes the rapid conduction of alkali metal ions by anchoring anions. The high dielectric nano-ceramic material promotes the uniform deposition of alkali metal ions through the action of a dynamic uniform electric field, avoiding the growth of metal dendrites and the appearance of cracks in the rigid all-solid-state alkali metal battery during the charge and discharge process. This design utilizes the mechanical flexibility of the polymer and the high dielectric properties of the ceramic material, and synergistically enhances the intrinsic alkali metal ion conductivity and alkali metal ion desolvation / diffusion kinetics of the interface, thereby achieving a good charge and discharge efficiency at a high current density. In addition, this structural design can effectively suppress side reactions inside the all-solid-state alkali metal battery, achieving fast charging and high efficiency performance of the all-solid-state alkali metal battery.

[0010] Preferably, the lithiated fluorine-containing polymer comprises a lithiated perfluorosulfonic acid-polytetrafluoroethylene copolymer (Li-Nafion). Li-Nafion can stabilize alkali metal negative electrode materials and promote rapid conduction of alkali metal ions through its fluorine-rich elastic component and the characteristics of anchoring anions.

[0011] Preferably, the weight average molecular weight of the lithiated perfluorosulfonic acid-polytetrafluoroethylene copolymer is 500g / mol-2000g / mol, preferably 600g / mol-1000g / mol, for example, it can be 500g / mol, 550g / mol, 600g / mol, 620g / mol, 650g / mol, 680g / mol, 700g / mol, 720g / mol, 750g / mol, 780g / mol, 800g / mol, 820g / mol, 850g / mol, 880g / mol, 900g / mol, 920g / mol, 950g / mol, 980g / mol, 1000g / mol, 1200g / mol, 1500g / mol, 1800g / mol, 2000g / mol, etc. The present invention regulates the weight average molecular weight of the lithiated perfluorosulfonic acid-polytetrafluoroethylene copolymer so that its fluorine-rich elastic component stabilizes the negative electrode and promotes the rapid conduction of alkali metal ions by anchoring anions. If a lithiated perfluorosulfonic acid-polytetrafluoroethylene copolymer with a lower weight average molecular weight is used, the amount of fluorine-containing components will be too small, resulting in poor negative electrode interface stability; if a lithiated perfluorosulfonic acid-polytetrafluoroethylene copolymer with a higher weight average molecular weight is used, the content of the lithiated fluorine-containing polymer will be too high, resulting in low overall ionic conductivity of the interface modification layer.

[0012] Preferably, the dielectric constant of the nano dielectric ceramic material is 1-20000, preferably 1000-3000, for example, it can be 1, 2, 5, 6, 10, 20, 50, 80, 100, 200, 500, 800, 1000, 1200, 1500, 1800, 2000, 2200, 2500, 2800, 3000, 3200, 3500, 3800, 4000, 5000, 8000, 10000, 12000, 15000, 18000, 20000, etc. If a nano dielectric ceramic material with a lower dielectric constant is used, it will lead to uneven electric field distribution, thereby causing uneven lithium ion deposition.

[0013] Preferably, the nano dielectric ceramic material includes any one of titanate, niobate or nitride or a combination of at least two thereof, preferably titanate.

[0014] Preferably, the titanate includes any one of barium titanate, magnesium titanate or calcium titanate, or a combination of at least two of them.

[0015] Preferably, the niobate includes any one of potassium niobate, sodium niobate, potassium sodium niobate or lithium niobate, or a combination of at least two thereof.

[0016] Preferably, the nitride comprises hexagonal boron nitride.

[0017] Preferably, the mass ratio of the lithiated fluoropolymer and the nano-dielectric ceramic material is (6-9):(1-4), preferably (6.5-8.5):(1.5-3.5), for example, it can be 6:4, 6.5:3.5, 7:3, 7.5:2.5, 8:2, 8.5:1.5, 9:1, etc. The present invention regulates the mass ratio of the lithiated fluoropolymer and the nano-dielectric ceramic material so that the two synergistically enhance the lithium ion conductivity and lithium ion desolvation / diffusion kinetics between the interfaces. If a lithiated fluoropolymer with a lower content is used, the content of its fluorine-rich elastic component will be reduced, resulting in a lower mechanical strength of the interface at the negative electrode; if a nano-dielectric ceramic material with a higher content is used, the lithium ion desolvation / diffusion kinetics will be slowed down.

[0018] In a second aspect, the present invention provides a method for preparing an interface modification layer for a solid alkali metal negative electrode according to the first aspect, the method comprising the following steps:

[0019] The lithiated fluorine-containing polymer, the nano dielectric ceramic material and the solvent are mixed to obtain an interface modification layer slurry; the interface modification layer slurry is dried to obtain the interface modification layer for the solid alkali metal negative electrode.

[0020] In the present invention, the method for preparing the lithiated fluorine-containing polymer comprises the following steps: stirring the fluorine-containing polymer and lithium hydroxide solution, and drying to obtain the lithiated fluorine-containing polymer.

[0021] In the present invention, the concentration of the lithium hydroxide solution is 1 mol / L to 2 mol / L, for example, it can be 1 mol / L, 1.2 mol / L, 1.5 mol / L, 1.8 mol / L, 2 mol / L, etc.

[0022] In the present invention, the stirring time is 5 h to 7 h, for example, 5 h, 5.5 h, 6 h, 6.5 h, 7 h, etc.

[0023] In the present invention, the drying temperature is 55°C to 65°C, for example, it can be 55°C, 58°C, 60°C, 62°C, 65°C, etc.; the drying time is 10h to 13h, for example, it can be 10h, 11h, 12h, 13h, etc.

[0024] Preferably, the solvent includes any one of N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, ethylene glycol dimethyl ether or acetonitrile, or a combination of at least two thereof.

[0025] Preferably, the solid content of the interface modification layer slurry is 4wt.% to 6wt.%, for example, 4wt.%, 4.2wt.%, 4.5wt.%, 4.8wt.%, 5wt.%, 5.2wt.%, 5.5wt.%, 5.8wt.%, 6wt.%, etc.

[0026] In a third aspect, the present invention provides a solid alkali metal negative electrode, comprising an alkali metal negative electrode and an interface modification layer arranged on at least one side of the alkali metal negative electrode, wherein the interface modification layer comprises the interface modification layer for a solid alkali metal negative electrode according to the first aspect.

[0027] Preferably, the thickness of the interface modification layer is 1 μm-5 μm, preferably 1 μm-2 μm, for example, 1 μm, 1.2 μm, 1.5 μm, 1.8 μm, 2 μm, 2.2 μm, 2.5 μm, 2.8 μm, 3 μm, 3.2 μm, 3.5 μm, 3.8 μm, 4 μm, 4.2 μm, 4.5 μm, 4.8 μm, 5 μm, etc. If a thinner interface modification layer is used, the compatibility between the solid electrolyte and the negative electrode will be poor; if a thicker interface modification layer is used, the ionic conductivity at the interface between the solid electrolyte and the negative electrode will be low.

[0028] The present invention also provides a method for preparing the solid alkali metal negative electrode, which comprises the following steps:

[0029] The interface modification layer slurry according to the second aspect is coated on at least one side of the alkali metal negative electrode, and then sliced ​​after drying to obtain the solid alkali metal negative electrode.

[0030] In the present invention, the alkali metal negative electrode exemplarily includes a lithium copper composite strip.

[0031] In a fourth aspect, the present invention provides an all-solid-state alkali metal battery, comprising a positive electrode, a negative electrode and a solid electrolyte, wherein the negative electrode comprises the solid-state alkali metal negative electrode according to the third aspect.

[0032] The all-solid-state alkali metal battery assembled by the solid-state alkali metal negative electrode provided by the present invention has good rate performance and cycle stability.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] The present invention provides an interface modification layer for a solid-state alkali metal negative electrode, which is used as an interface regulator for an all-solid-state alkali metal battery by compounding a single-ion conductive lithiated fluorinated polymer with a high dielectric nano-ceramic material, thereby reducing the side reaction between the alkali metal negative electrode and the electrolyte, thereby stabilizing the cycle performance of the all-solid-state alkali metal battery.

[0035] Specifically, the lithiated fluorinated polymer stabilizes the negative electrode through the fluorine-rich elastic component it contains, and promotes the rapid conduction of alkali metal ions by anchoring anions. The high dielectric nanoceramic material promotes the uniform deposition of alkali metal ions through the action of a dynamic uniform electric field, avoiding the growth of metal dendrites and the appearance of cracks in the rigid all-solid-state alkali metal battery during the charge and discharge process. This design utilizes the mechanical flexibility of the polymer and the high dielectric properties of the ceramic material to synergistically enhance the intrinsic alkali metal ion conductivity and alkali metal ion desolvation / diffusion kinetics of the interface, thereby achieving better charge and discharge efficiency at high current density. In addition, this structural design can also effectively suppress side reactions within the all-solid-state alkali metal battery, achieving fast charging and high efficiency performance of the all-solid-state alkali metal battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The charge and discharge curve diagram of the all-solid-state lithium metal battery provided for Application Example 1. DETAILED DESCRIPTION

[0037] The technical solution of the present invention is further described below by combining the accompanying drawings and specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0038] Example 1

[0039] The present embodiment provides an interface modification layer and a solid lithium metal negative electrode comprising the same, wherein the solid lithium metal negative electrode comprises a lithium copper composite belt and an interface modification layer disposed on one side of the lithium copper composite belt. The material of the interface modification layer comprises a lithium perfluorosulfonic acid-polytetrafluoroethylene copolymer (Li-Nafion) having a weight average molecular weight of 1000 g / mol and a nano dielectric barium titanate material having a dielectric constant of 2000. The mass ratio of the lithium perfluorosulfonic acid-polytetrafluoroethylene copolymer to the nano dielectric barium titanate material is 7:3.

[0040] This embodiment also provides a method for preparing the above-mentioned interface modification layer and solid lithium metal negative electrode, which comprises the following steps:

[0041] S1. Add perfluorosulfonic acid-polytetrafluoroethylene copolymer powder to 50 mL of 1.0 mol / L lithium hydroxide aqueous solution and stir for 6 h, then centrifuge to obtain a solid, and dry the solid at 60° C. for 12 h to obtain Li-Nafion powder.

[0042] S2. The Li-Nafion powder and the nano dielectric barium titanate material in step S1 are dissolved in dimethyl sulfoxide in a mass ratio of 7:3, and stirred and ultrasonically dispersed to form a uniform interface modification layer slurry with a solid content of 5wt.%; the interface modification layer slurry is then coated on a lithium copper composite tape and dried, and cut into discs with a diameter of 10mm to obtain the solid lithium metal negative electrode, wherein the thickness of the interface modification layer is 1.5μm, and the total loading amount of the Li-Nafion powder and the nano dielectric barium titanate material is 0.4mg / cm 2 .

[0043] Example 2

[0044] The present embodiment provides an interface modification layer and a solid lithium metal negative electrode comprising the same, wherein the solid lithium metal negative electrode comprises a lithium copper composite belt and an interface modification layer disposed on one side of the lithium copper composite belt. The material of the interface modification layer comprises a lithium perfluorosulfonic acid-polytetrafluoroethylene copolymer (Li-Nafion) having a weight average molecular weight of 1300 g / mol and a nano dielectric barium titanate material having a dielectric constant of 2000. The mass ratio of the lithium perfluorosulfonic acid-polytetrafluoroethylene copolymer to the nano dielectric barium titanate material is 7.5:2.5.

[0045] This embodiment also provides a method for preparing the above-mentioned interface modification layer and solid lithium metal negative electrode, which comprises the following steps:

[0046] S1. Add perfluorosulfonic acid-polytetrafluoroethylene copolymer powder to 50 mL of 1.0 mol / L lithium hydroxide aqueous solution and stir for 6 h, then centrifuge to obtain a solid, and dry the solid at 60° C. for 12 h to obtain Li-Nafion powder.

[0047] S2. The Li-Nafion powder and the nano-dielectric barium titanate material in step S1 are dissolved in dimethyl sulfoxide in a mass ratio of 7.5:2.5, and stirred and ultrasonically dispersed to form a uniform interface modification layer slurry with a solid content of 5wt.%; the interface modification layer slurry is then coated on a lithium copper composite tape and dried, and cut into discs with a diameter of 10mm to obtain the solid lithium metal negative electrode, wherein the thickness of the interface modification layer is 1.6μm, and the total loading amount of the Li-Nafion powder and the nano-dielectric barium titanate material is 0.4mg / cm 2 .

[0048] Example 3

[0049] The present embodiment provides an interface modification layer and a solid lithium metal negative electrode comprising the same, wherein the solid lithium metal negative electrode comprises a lithium copper composite belt and an interface modification layer disposed on one side of the lithium copper composite belt. The material of the interface modification layer comprises a lithium perfluorosulfonic acid-polytetrafluoroethylene copolymer (Li-Nafion) having a weight average molecular weight of 1800 g / mol and a nano dielectric barium titanate material having a dielectric constant of 2000. The mass ratio of the lithium perfluorosulfonic acid-polytetrafluoroethylene copolymer to the nano dielectric barium titanate material is 6.5:3.5.

[0050] This embodiment also provides a method for preparing the above-mentioned interface modification layer and solid lithium metal negative electrode, which comprises the following steps:

[0051] S1. Add perfluorosulfonic acid-polytetrafluoroethylene copolymer powder to 50 mL of 1.0 mol / L lithium hydroxide aqueous solution and stir for 6 h, then centrifuge to obtain a solid, and dry the solid at 60° C. for 12 h to obtain Li-Nafion powder.

[0052] S2. The Li-Nafion powder and the nano-dielectric barium titanate material in step S1 are dissolved in dimethyl sulfoxide in a mass ratio of 6.5:3.5, and a uniform interface modification layer slurry with a solid content of 5 wt.% is formed after stirring and ultrasonic dispersion; the interface modification layer slurry is then coated on a lithium copper composite tape and dried, and cut into discs with a diameter of 10 mm to obtain the solid lithium metal negative electrode, wherein the thickness of the interface modification layer is 1.4 μm, and the total loading amount of the Li-Nafion powder and the nano-dielectric barium titanate material is 0.4 mg / cm 2 .

[0053] Example 4

[0054] The difference between this embodiment and embodiment 1 is that the nano dielectric barium titanate material is replaced with an equal mass of nano dielectric magnesium titanate material, and the rest is the same as embodiment 1.

[0055] Example 5

[0056] The difference between this embodiment and embodiment 1 is that the dielectric constant of the nano dielectric barium titanate material is 1000, and the rest is the same as embodiment 1.

[0057] Example 6

[0058] The difference between this embodiment and embodiment 1 is that the nano dielectric barium titanate material is replaced with an equal mass of aluminum oxide, and the rest is the same as embodiment 1.

[0059] Example 7

[0060] The difference between this embodiment and embodiment 1 is that the mass ratio of the lithiated perfluorosulfonic acid-polytetrafluoroethylene copolymer to the nano dielectric barium titanate material is 4:6, and the rest is the same as embodiment 1.

[0061] Example 8

[0062] The difference between this embodiment and embodiment 1 is that the mass ratio of the lithiated perfluorosulfonic acid-polytetrafluoroethylene copolymer to the nano dielectric barium titanate material is 5:5, and the rest is the same as embodiment 1.

[0063] Example 9

[0064] The difference between this embodiment and embodiment 1 is that the thickness of the interface modification layer is 900 nm, and the rest is the same as embodiment 1.

[0065] Example 10

[0066] The difference between this embodiment and embodiment 1 is that the thickness of the interface modification layer is 10 μm, and the rest is the same as embodiment 1.

[0067] Comparative Example 1

[0068] The difference between this comparative example and Example 1 is that Li-Nafion is replaced with an equal mass of nano dielectric barium titanate material, and the rest is the same as Example 1.

[0069] Comparative Example 2

[0070] The difference between this comparative example and Example 1 is that Li-Nafion is replaced by polyvinylidene fluoride of equal mass, and the rest is the same as Example 1.

[0071] Comparative Example 3

[0072] The difference between this comparative example and Example 1 is that the nano dielectric barium titanate material is replaced with Li-Nafion of equal mass, and the rest is the same as Example 1.

[0073] Comparative Example 4

[0074] The difference between this comparative example and Example 1 is that Li-Nafion is replaced by polyacrylonitrile of equal mass, and the rest is the same as Example 1.

[0075] Comparative Example 5

[0076] This comparative example provides a bare lithium-copper composite strip.

[0077] Application Examples 1 to 10 and Comparative Application Examples 1 to 5

[0078] The solid-state lithium metal negative electrodes provided in Examples 1 to 10 and Comparative Examples 1 to 5 are assembled to obtain an all-solid-state lithium metal battery, and the preparation method is as follows:

[0079] In an argon glove box, 100 mg of Li6PS5Cl (purchased from CROOD) solid electrolyte was placed in an alumina ceramic sleeve with a diameter of 10 mm in the mold battery and compacted into a powder cake state by cold pressing, where the cold pressing pressure was 200 MPa.

[0080] 20 mg of positive electrode active material (LiNi 0.83 Co 0.11 Mn 0.06 O2) is placed on one side of the sleeve, and a pressure of 300Mpa is used to cold-press and compact the solid electrolyte surface as a positive electrode layer. A piece of aluminum foil with a thickness of 20μm is stacked on one side of the positive electrode layer, thereby forming a collector on the positive electrode side to obtain a positive electrode sheet. The solid lithium metal negative electrode provided in the above embodiment and the comparative example is placed on the other side of the solid electrolyte layer in contact with the positive electrode sheet as a negative electrode sheet, and the negative electrode sheet is further fully contacted with the solid electrolyte layer under a pressure of 10Mpa to obtain a stack consisting of a positive electrode sheet, a solid electrolyte layer and a negative electrode sheet in sequence. Stainless steel collectors are arranged above and below the stack, and collector leads are attached to the collectors to assemble an all-solid-state lithium metal battery.

[0081] Test conditions

[0082] The all-solid-state lithium metal batteries provided in Application Examples 1 to 10 and Comparative Application Examples 1 to 5 were tested, and the testing method was as follows:

[0083] (1) Impedance test

[0084] The tests were performed with an MTZ-35 electrochemical impedance analyzer with an amplitude of 5 mV and a range of 1 MHz to 0.1 Hz.

[0085] (2) Electrochemical test

[0086] The assembled all-solid-state lithium metal battery was placed in a 35°C constant temperature box, and the electrochemical performance test was carried out using the LAND CT2001A battery testing system. The cycle performance test was carried out at a rate of 1C / 1C, and the cycle performance test at a large rate of 3C / 3C was carried out. The test voltage range was 2.5 to 4.25V.

[0087] The test results are shown in Table 1:

[0088] Table 1

[0089]

[0090]

[0091] From Table 1 and Figure 1 It can be seen that the present invention adjusts the composition of the interface modification layer so that the prepared solid-state lithium metal negative electrode assembled to obtain an all-solid-state lithium metal battery has a high first coulombic efficiency. In the present invention, Examples 1 to 5 further optimize the mass ratio of the lithiated fluorinated polymer to the high dielectric nanoceramic material, as well as the physical properties of the lithiated fluorinated polymer and the high dielectric nanoceramic material, so that the prepared interface modification layer synergistically enhances the intrinsic alkali metal ion conductivity and alkali metal ion desolvation / diffusion kinetics of the interface, thereby achieving better charge and discharge efficiency at high current density and reducing impedance.

[0092] By comparing Example 1 with Example 6, it can be seen that by using a low dielectric constant alumina ceramic material, it is impossible to further control the uniform deposition of lithium ions, resulting in poor cycle performance of the all-solid-state lithium metal battery and high internal impedance.

[0093] By comparing Example 1 with Examples 7-8, it can be seen that the present invention adjusts the mass ratio of the lithiated fluorinated polymer and the nano-dielectric ceramic material so that the two synergistically enhance the lithium ion conductivity and lithium ion desolvation / diffusion kinetics at the interface.

[0094] By comparing Example 1 with Example 9-Example 10, it can be seen that the present invention achieves good compatibility and rapid lithium ion transmission between the solid electrolyte and the alkali metal negative electrode by regulating the thickness of the interface modification layer.

[0095] By comparing Example 1, Comparative Example 1 and Comparative Example 3, it can be seen that the lithiated fluorinated polymer and the high dielectric nano-ceramic material have a synergistic effect and are indispensable to each other, which synergistically improve the fast charge and discharge performance of the all-solid-state lithium metal battery and reduce the internal impedance.

[0096] Comparison of Example 1, Comparative Example 2 and Comparative Example 4 shows that conventional polymers cannot achieve the technical effect of lithiated fluorinated polymers.

[0097] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. An interface modification layer for a solid alkali metal negative electrode, characterized in that: The material of the interface modification layer includes lithiated fluorine-containing polymer and nano dielectric ceramic material.

2. The interface modification layer according to claim 1, characterized in that: The lithiated fluorinated polymer includes a lithiated perfluorosulfonic acid-polytetrafluoroethylene copolymer; Preferably, the weight average molecular weight of the lithiated perfluorosulfonic acid-polytetrafluoroethylene copolymer is 500 g / mol-2000 g / mol, preferably 600 g / mol-1000 g / mol.

3. The interface modification layer according to claim 1 or 2, characterized in that: The dielectric constant of the nano dielectric ceramic material is 1-20000, preferably 1000-3000.

4. The interface modification layer according to any one of claims 1 to 3, characterized in that The nano dielectric ceramic material includes any one of titanate, niobate or nitride or a combination of at least two thereof, preferably titanate; Preferably, the titanate includes any one of barium titanate, magnesium titanate or calcium titanate, or a combination of at least two thereof; Preferably, the niobate includes any one of potassium niobate, sodium niobate, potassium sodium niobate or lithium niobate, or a combination of at least two thereof; Preferably, the nitride comprises hexagonal boron nitride.

5. The interface modification layer according to any one of claims 1 to 4, characterized in that The mass ratio of the lithiated fluorine-containing polymer to the nano dielectric ceramic material is (6-9):(1-4), preferably (6.5-8.5):(1.5-3.5).

6. A method for preparing an interface modification layer for a solid alkali metal negative electrode according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: The lithiated fluorine-containing polymer, the nano dielectric ceramic material and the solvent are mixed to obtain an interface modification layer slurry; the interface modification layer slurry is dried to obtain the interface modification layer for the solid alkali metal negative electrode.

7. The method according to claim 6, characterized in that The solvent includes any one or a combination of at least two of N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, ethylene glycol dimethyl ether or acetonitrile; Preferably, the solid content of the interface modification layer slurry is 4 wt.% to 6 wt.%.

8. A solid alkali metal negative electrode, characterized in that: The solid alkali metal negative electrode comprises an alkali metal negative electrode and an interface modification layer disposed on at least one side of the alkali metal negative electrode, wherein the interface modification layer comprises the interface modification layer for a solid alkali metal negative electrode according to any one of claims 1 to 5.

9. The solid alkali metal negative electrode according to claim 8, characterized in that: The thickness of the interface modification layer is 1 μm-5 μm, preferably 1 μm-2 μm.

10. An all-solid-state alkali metal battery, characterized in that: The all-solid-state alkali metal battery comprises a positive electrode, a negative electrode and a solid electrolyte, and the negative electrode comprises the solid-state alkali metal negative electrode according to claim 8 or 9.